Direct Observation of Plasmon Band Formation and Delocalization in Quasi-Infinite Nanoparticle Chains - Mayer, Martin; Potapov, Pavel L.; Pohl, Darius; Steiner, Anja Maria; Schultz, Johannes; Rellinghaus, Bernd; Lubk, Axel; Koenig, Tobias A. F.; Fery, Andreas (Nano Letters, 2019)
Chains of metallic nanoparticles sustain strongly confined surface plasmons with relatively low dielectric losses. To exploit these properties in applications, such as waveguides, the fabrication of long chains of low disorder and a thorough understanding of the plasmon-mode properties, such as dispersion relations, are indispensable. Here, we use a wrinkled template for directed self-assembly to assemble chains of gold nanoparticles. With this up-scalable method, chain lengths from two particles (140 nm) to 20 particles (1500 nm) and beyond can be fabricated. Electron energy-loss spectroscopy supported by boundary element simulations, finite-difference time-domain, and a simplified dipole coupling model reveal the evolution of a band of plasmonic waveguide modes from degenerated single-particle modes in detail. In striking difference from plasmonic rod-like structures, the plasmon band is confined in excitation energy, which allows light manipulations below the diffraction limit. The non-degenerated surface plasmon modes show suppressed radiative losses for efficient energy propagation over a distance of 1500 nm.
CRIS-Team Scopus Importer:2022-04-14
Keywords: electron-energy loss spectroscopy; nanoparticle; plasmonic polymer; Surface plasmons; template-assisted self-assembly